2022
DOI: 10.1111/iju.14978
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity and safety of two doses of SARS‐CoV‐2 mRNA vaccine in kidney transplant recipients with low‐dose rituximab

Abstract: Objectives We evaluated whether the treatment history of low‐dose rituximab affected safety profiles, and humoral and cellular responses induced by severe acute respiratory syndrome coronavirus 2 messenger ribonucleic acid vaccine in healthy controls and kidney transplant recipients. Methods We enrolled 10 healthcare workers as controls, 22 kidney transplant recipients with rituximab, and 36 kidney transplant recipients without rituximab without history of coronavirus d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 23 publications
(69 reference statements)
1
9
1
Order By: Relevance
“…In previous studies, immunosuppressants, including steroids, MMF, belatacept, and triple immunosuppression; elderly patients; short period from transplantation; low lymphocyte counts; and low allograft function were confirmed as risk factors for negative immunogenicity after the third vaccination ( 8 , 10 15 ). Age > 60 years, low lymphocyte counts, and transplantation within 2 years were identified as risk factors in our study; however, immunosuppressants, including MMF, did not affect the anti-SARS-CoV-2 antibody positivity rate in our study, even though MMF was confirmed as a risk factor for a negative humoral response after the second SARS-CoV-2 mRNA vaccine in our previous study ( 16 ). MMF did not affect the seropositivity rate; however, the anti-SARS-CoV-2 antibody titer was significantly lower in KTRs with MMF.…”
Section: Discussioncontrasting
confidence: 70%
See 4 more Smart Citations
“…In previous studies, immunosuppressants, including steroids, MMF, belatacept, and triple immunosuppression; elderly patients; short period from transplantation; low lymphocyte counts; and low allograft function were confirmed as risk factors for negative immunogenicity after the third vaccination ( 8 , 10 15 ). Age > 60 years, low lymphocyte counts, and transplantation within 2 years were identified as risk factors in our study; however, immunosuppressants, including MMF, did not affect the anti-SARS-CoV-2 antibody positivity rate in our study, even though MMF was confirmed as a risk factor for a negative humoral response after the second SARS-CoV-2 mRNA vaccine in our previous study ( 16 ). MMF did not affect the seropositivity rate; however, the anti-SARS-CoV-2 antibody titer was significantly lower in KTRs with MMF.…”
Section: Discussioncontrasting
confidence: 70%
“…Of the 58 KTRs who were enrolled in a study that evaluated the immunogenicity of two doses of SARS-CoV-2 mRNA in KTRs at our department, 54 KTRs were enrolled in this study ( 16 ). All participants completed three doses of the SARS-CoV-2 mRNA-1273 vaccine (Moderna) or BNT162b2 SARS-CoV-2 mRNA vaccine (Pfizer-BioNTech) between January and June 2022.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations